The introduction of formal insurance and its effect on redistribution - Dan Anderberg; Karlijn Marsink (Center for Economic Studies and ifo Institute (CESifo), 2019)
Transfers motivated by altruism, norms of giving, and guilt play an important role in supporting individuals who suffer losses due to risk. We present empirical evidence from an artefactual field experiment in Ethiopia in which we introduce formal insurance in a setting where donors make redistributive transfers to anonymously paired recipients. We find that donors reduce their transfers to recipients who don't take-up insurance, and that this effect is larger for donors who hold the ex ante belief that the recipient is more likely to take-up insurance. The findings are consistent with a model of a norm of giving where donors feel guilty for deviating from the norm. The feelings of guilt decline with the expected social distance, that is revealed by the recipients' observable insurance uptake decisions. The model highlights how the introduction of formal insurance may erode norms of giving and lead vulnerable groups to face more volatile consumption.
Keywords: D64; D91; G22; O16; O17; 330; formal insurance; transfers; norms of giving; guilt; social distance